PENGUATAN KESIAPSIAGAAN BENCANA DI DESA TOTOPO: IMPLEMENTASI JALUR EVAKUASI DAN TITIK KUMPUL BERBASIS GEOLOGI UNTUK MENGHADAPI BAHAYA BANJIR DAN LONGSOR - Meidji, Icha Untari (Universitas Patria Artha, 2024)
Totopo Village is an area located in Bilato District, Gorontalo Province. This are is one of the remote villages that is highly vulnerable to various types of disasters. The topography of the village is dominated by hills, with houses located in the valley, adjacent to a large river that often causes flooding and submerges settlements around Totopo Village. The hills in this village are mostly bare, and some of them are used by residents to grow secondary crops, crops that do not have a strong ability to bind the soil, thus becoming one of the triggering factors for landslides. In 2022, there was a major flood and landslide that made this village isolated. The purpose of this community service is to improve the preparedness of the community of Totopo Village, Gorontalo Province, especially in facing floods and landslides. Identification of locations for the installation of evacuation routes and gathering points based on geological topographic interpretation resulted in 2 gathering points. The results of this community service are the installation of 5 evacuation route signs and 2 gathering point signs installed around Totopo Village.